Allosteric Activation of 15‐Lipoxygenase‐1 by Boswellic Acid Induces the Lipid Mediator Class Switch to Promote Resolution of Inflammation. Issue 6 (25th December 2022) - Börner, Friedemann; Pace, Simona; Jordan, Paul M.; Gerstmeier, Jana; Gomez, Mario; Rossi, Antonietta; Gilbert, Nathaniel C.; Newcomer, Marcia E.; Werz, Oliver
Abstract: Specialized pro‐resolving mediators (SPM), primarily produced in innate immune cells, exert crucial bioactions for resolving inflammation. Among various lipoxygenases (LOX), 15‐LOX‐1 is key for SPM biosynthesis, but cellular activation principles of 15‐LOX‐1 are unexplored. It was shown that 3‐ O ‐acetyl‐11‐keto‐ β ‐boswellic acid (AKBA) shifts 5‐LOX regiospecificity from 5‐ to 12‐lipoxygenation products. Here, it is demonstrated that AKBA additionally activates cellular 15‐LOX‐1 via an allosteric site accomplishing robust SPM formation in innate immune cells, particularly in M2 macrophages. Compared to ionophore, AKBA‐induced LOX activation is Ca 2+ ‐ and phosphorylation‐independent, with modest induction of 5‐LOX products. AKBA docks into a groove between the catalytic and regulatory domains of 15‐LOX‐1 interacting with R98; replacement of R98 by alanine abolishes AKBA‐induced 15‐LOX product formation in HEK293 cells. In zymosan‐induced murine peritonitis, AKBA strikingly elevates SPM levels and promotes inflammation resolution. Together, targeted allosteric modulation of LOX activities governs SPM formation and offers new concepts for inflammation resolution pharmacotherapy. Abstract : A boswellic acid is discovered as a molecular switch enabling innate immune cells to block formation of pro‐inflammatory eicosanoids and to generate specialized pro‐resolving mediators by modulation of lipoxygenase isoforms at allosteric sites. These findings advance inflammation resolution pharmacology and may give direction for development of new therapeutics for treating diseases connected to unresolved inflammation.